2023
DOI: 10.1038/s41598-023-38238-y
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cartilage and subchondral bone cysts on knee specimens based on a spectral photon-counting computed tomography

Abstract: Spectral photon-counting computed tomography (SPCCT) is a new technique with the capability to provide mono-energetic (monoE) images with high signal to noise ratio. We demonstrate the feasibility of SPCCT to characterize at the same time cartilage and subchondral bone cysts (SBCs) without contrast agent in osteoarthritis (OA). To achieve this goal, 10 human knee specimens (6 normal and 4 with OA) were imaged with a clinical prototype SPCCT. The monoE images at 60 keV with isotropic voxels of 250 × 250 × 250 µ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Spectral imaging can also be used for imaging of joint spaces and delineation of small cartilage defects after intraarticular contrast injection [9,59,60]. A recently published study by Garcelon et al showed the ability of spectral imaging to visualize cartilage and subchondral cysts on knee CT without using contrast agent in cases with osteoarthritis [61].…”
Section: Spectral Imagingmentioning
confidence: 99%
“…Spectral imaging can also be used for imaging of joint spaces and delineation of small cartilage defects after intraarticular contrast injection [9,59,60]. A recently published study by Garcelon et al showed the ability of spectral imaging to visualize cartilage and subchondral cysts on knee CT without using contrast agent in cases with osteoarthritis [61].…”
Section: Spectral Imagingmentioning
confidence: 99%